Event History Analysis of Grievance Arbitration in Ontario: Labour Justice Delayed? - Curran, Bruce (Relations industrielles / Industrial Relations, 2017)
SummaryA number of empirical studies from the early 1970s to the mid-1990s indicated that delay in Canadian grievance arbitration was becoming an increasing problem. There have been no further scientific studies on delay since then, despite developments that may exacerbate the issue like increased legalism and expanded arbitral jurisdiction. Academics and practitioners have recently voiced renewed concerns about the threat that delay poses to the viability of the grievance arbitration system.To address this gap in the scientific literature, the present study examines delay and its determinants in Ontario over the last two decades. Content analysis was conducted on a random sample of almost 400 Ontario grievance arbitrations from three reference years (1994, 2004, and 2012). I then performed event history analysis on the data to determine the various factors that were associated with delay. Consistent with common perception, my empirical results suggest that delay has become worse over the past two decades. I find that certain legalistic factors are indeed associated with delay, including the use of lawyers, the use of preliminary objections, the number of witnesses testifying, and attacks on credibility. In terms of expanded arbitral jurisdiction, I find that while delay has increased for grievances involving alleged Employment Standards Act violations, for all other non-traditional issues (including human rights complaints) there are no significant increases. The results also show that certain dispute resolution procedures, such as expedited arbitration and the use of sole arbitrators are related to shorter grievance durations, and this, combined with the other findings, suggests practical solutions to the issue of delay. However, the findings also suggest that the use of certain procedures involving additional steps, like settlement and mediation-arbitration, can also serve to increase grievance duration when used unsuccessfully.